نحو تأسيس نظرية للعنوان من منظور سيميائي – تداولي - فهيمة, لحلوحي (Sciences humaines; Vol. 23 (2011): SCIENCES HUMAINES, 2014)
مما لا شك فيه أن دراسة موضوع نظرية العنوان من منظور سيميائي -تداولي يعني الكشف عن جوهر ظاهرة العنوان كظاهرة أدبية ونقدية، تطرح إشكالات منها: أولا وقبل كل شيء تعريف العنوان، ثم تحديد أنواع العنوان، وكذلك تعيين العلاقات بين العنوان وبنية النص، وأخيرا توضيح وظائف العنوان وأصنافها. يسعى هذا العمل إلى الإجابة على هذه الإشكالات المطروحة.   The main objective of this research is to carry out an investigation into the theory of title in literary works from a semiotic pragmatic perspective. This implies that the essence or the core of the concept of title should be explored as a literary and critical phenomenon. Through out the study, we intend to come up with a definition of the title, determine the categories of titles, gives full account of the link between title and the structure of the text, and finally explore the different functions of title. The present research aim at coming up to terms with the aforementioned issues.